2018
DOI: 10.26633/rpsp.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes del gasto de bolsillo en salud de la población pobre atendida en servicios de salud públicos en Perú, 2010–2014

Abstract: RESUMEN Objetivo El objetivo de este estudio fue averiguar qué factores afectan el gasto de bolsillo en servicios de salud prestados por el MINSA y los gobiernos regionales a la población en condiciones de pobreza monetaria relativa entre 2010 y 2014. Materiales y métodos Estudio transversal descriptivo econométrico con cortes anuales (2010-2014) a nivel nacional con información de encuestas de hogares. La variable dependiente fue el gasto de bolsillo en sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 6 publications
1
17
0
7
Order By: Relevance
“…Our results indicate that the probability of CHE in these cases would have been decreased by 13% and 19%, if these households had access to financial protection for hospital costs or for medication costs, respectively. By means of comparison, in Peru, expenses for medicines represented 44% of OOP expenditure for families with social security, compared to 62% for families that were not affiliated with this program (Petrera Pavone and Jiménez Sánchez, 2018 ), indicating the necessity to incorporate strategies for increasing both availability as well as accessibility of financial protection for households caring for a person with an MD.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the probability of CHE in these cases would have been decreased by 13% and 19%, if these households had access to financial protection for hospital costs or for medication costs, respectively. By means of comparison, in Peru, expenses for medicines represented 44% of OOP expenditure for families with social security, compared to 62% for families that were not affiliated with this program (Petrera Pavone and Jiménez Sánchez, 2018 ), indicating the necessity to incorporate strategies for increasing both availability as well as accessibility of financial protection for households caring for a person with an MD.…”
Section: Discussionmentioning
confidence: 99%
“…Si en el hogar se incrementa un perceptor de ingresos la probabilidad de convertirse en hogar pobre es 14,4%, un asegurado más en el hogar la probabilidad de ser hogar pobre es 13,6%. Una mujer fértil más en el hogar con niños menores o iguales a 5 años, las probabilidades de ser hogar pobre aumentan en 50,0% y 31,0% respectivamente 20 .…”
Section: Discussionunclassified
“…Global literature has indicated that health systems with greater utilization of public sector were likely to have lower levels of OOPE [146,147]. Some studies from LMICs have shown that only those utilizing public facilities could avoid OOPE [148]. Some South East Asian LMICs like Srilanka, Malaysia and Thailand achieved remarkably low levels of CHE by relying mainly on public-sector based healthcare delivery and this form of nancing has been found to be pro-poor [92,[149][150][151].…”
Section: Discussionmentioning
confidence: 99%